Exploration and Identification of Gliocladium sp as Biological Agent from the Rhizosphere of Tomato : Eksplorasi dan Identifikasi Jamur Gliocladium sp sebagai Agens Hayati dari Rhizosfer Tanaman Tomat - Mukaromah, Berliana Dwi; Bahri, Saiful; Indahsari, Wiwin Misnati Nur (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
One of the roles of microorganisms is as a biological agent. This study aims to explore and identify the biological agent of the fungus Gliocladium sp. found in the rhizosphere of tomato plants. Exploration was done by taking samples of tomato plant root soil in five locations using a diagonal plot. Rhizosphere microorganisms were isolated using the multilevel dilution and spread on PDA media added with chloramphenicol. Fungal isolates were identified macroscopically and microscopically. The results of exploring fungal biological agents in the rhizosphere soil of tomato plants revealed four genera of fungal isolates, namely Aspergillus, Trichoderma, Paecilomyces, and Gliocladium. Based on the identification results, the fungal isolate Gliocladium sp. has a blackish-green colony color with a circular colony. In contrast, microscopically, it has the morphological characteristics of upright conidiophores, growing straight, and branching.